Ground-state properties of light kaonic nuclei signaling symmetry energy at high densities - 杨荣瑶;韦斯纳;蒋维洲 (Chinese physics C, 2018)
A sensitive correlation between the ground-state properties of light kaonic nuclei and the symmetry energy at high densities is constructed under the framework of relativistic mean-field theory. Taking oxygen isotopes as an example, we see that a high-density core is produced in kaonic oxygen nuclei, due to the strongly attractive antikaonnucleon interaction. It is found that the 1 S_（1/2） state energy in the high-density core of kaonic nuclei can directly probe the variation of the symmetry energy at supranormal nuclear density, and a sensitive correlation between the neutron skin thickness and the symmetry energy at supranormal density is established directly. Meanwhile, the sensitivity of the neutron skin thickness to the low-density slope of the symmetry energy is greatly increased in the corresponding kaonic nuclei. These sensitive relationships are established upon the fact that the isovector potential in the central region of kaonic nuclei becomes very sensitive to the variation of the symmetry energy. These findings might provide another perspective to constrain high-density symmetry energy, and await experimental verification in the future.